2015
DOI: 10.3390/su7066336
|View full text |Cite
|
Sign up to set email alerts
|

Managing Sustainability Aspects in Renovation Processes: Interview Study and Outline of a Process Model

Abstract: Abstract:In many European countries, there are building stocks in need of extensive renovation. This constitutes an important opportunity to perform energy-saving measures and improve indoor environmental quality aiming at a more sustainable built environment. In this paper, we report results from an interview study with the aim of obtaining an in-depth understanding of renovation processes and how sustainability aspects are handled by various Swedish property owners. Examples of important barriers revealed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
2
30
0
4
Order By: Relevance
“…The question arises whether or not the adoption of LCC really is as slow as claimed, or if there is a discrepancy between the way researchers idealistically picture how LCC should be used and practitioners' ways of using LCC in practice. In a recent study about construction clients it was in fact found that the vast majority used LCC within their organization (Gluch & Gustafsson, 2015), which agrees with the interview observations made by Olsson et al (2015). However, Olsson et al (2015) found a large variation in the way LCC was used.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…The question arises whether or not the adoption of LCC really is as slow as claimed, or if there is a discrepancy between the way researchers idealistically picture how LCC should be used and practitioners' ways of using LCC in practice. In a recent study about construction clients it was in fact found that the vast majority used LCC within their organization (Gluch & Gustafsson, 2015), which agrees with the interview observations made by Olsson et al (2015). However, Olsson et al (2015) found a large variation in the way LCC was used.…”
Section: Introductionsupporting
confidence: 74%
“…In a recent study about construction clients it was in fact found that the vast majority used LCC within their organization (Gluch & Gustafsson, 2015), which agrees with the interview observations made by Olsson et al (2015). However, Olsson et al (2015) found a large variation in the way LCC was used. Taken together, this points to a disparity between researchers' and practitioners' perception about the level and type of use of LCC in construction and real estate, necessitating the investigation about the practice of LCC, including practitioners' rationales for LCC adoption and a mapping of their uses for it in practice.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations